Therapeutic efficacy of rose oil: A comprehensive review of clinical evidence - Safieh Mohebitabar; Mahbobeh Shirazi; Sodabeh Bioos; Roja Rahimi; Farhad Malekshahi; Fatemeh Nejatbakhsh (Mashhad University of Medical Sciences, 2017)
Objective: Rose oil is obtained from the petals of difference Rosa species especially Rosa centifolia L. and Rosa damascena Mill. Various pharmacological properties have been attributed to rose oil. The aim of the present study was to review the rose oil therapeutic effects which had been clinically evaluated in trial studies. Materials and Methods: Google scholar, PubMed, Cochrane Library, and Scopus were searched for human studies which have evaluated the therapeutic effects of rose oil and published in English language until August 2015. Results: Thirteen clinical trials (772 participants) were included in this review. Rose oil was administered via inhalation or used topically. Most of the studies (five trials) evaluated the analgesic effect of rose oil. Five studies evaluated the physiological relaxation effect of rose oil. Anti-depressant, psychological relaxation, improving sexual dysfunction, and anti-anxiety effects were the other clinical properties reported for rose oil. Conclusion: Numerous studies on the pharmacological properties of rose oil have been done in animals, but studies in humans are few.  In this study, it was observed that rose oil had physiological and psychological relaxation, analgesic and anti-anxiety effects. To obtain conclusive results on the efficacy and safety of rose oil, further clinical trials with larger sample size and better designation are required.